Yield losses of asymptomatic strawberry plants infected with Strawberry mild yellow edge virus - Torrico Ramallo, Ada Karina (2017)
After successive vegetative propagation cycles, strawberry (Fragaria × ananassa Duch.) plants often accumulate multiple virus species that result in viral symptoms and losses in yield and quality. However, strawberry plants infected by a single virus species usually remain asymptomatic with unknown effects on fruit production and quality. In this context, the effect of Strawberry mild yellow edge virus (SMYEV) on fruit production was studied in strawberry plants, cultivar Camarosa, over two years. Asymptomatic SMYEV-infected plants showed a significant reduction in total and marketable fruit number and weight compared with healthy plants. These reductions ranged between 28% and 63%, depending on the parameter measured and the production cycle. Fluctuations in SMYEV concentration in the plants was detected throughout the crop cycle, suggesting that samples for virus diagnosis should be taken when the plant has the highest virus concentration; in this study, this occurred at the end of the crop cycle. These results show that analyzing symptomless strawberry plants should be part of a virus disease management plant and an important component to control the quantitative and qualitative impacts of SMYEV on strawberry yield.